2013
DOI: 10.1016/j.jaap.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The intermediate pyrolysis of de-inking sludge to produce a sustainable liquid fuel

Abstract: De-inking sludge is a waste product generated from secondary fibre paper mills who manufacture recycled paper into new paper sheets; it refers directly to the solid residues which evolve during the de-inking stage of the paper pulping process. The current practice for the disposal of this waste is either by landspreading, landfilling or incineration which is unsustainable. This work has explored the intermediate pyrolysis of pre-conditioned de-inking sludge pellets in a recently patented 20 kg/h intermediate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 9 publications
(7 reference statements)
3
52
0
Order By: Relevance
“…A high ash content was detected in the sewage sludge (76.2 %) and paper sludge (82.3 %) biochars in agreement with other studies, and the resulting HHVs were lower than that of the corresponding feedstocks at 5.9 and 3.6 MJ kg −1 , respectively.…”
Section: Resultssupporting
confidence: 91%
“…A high ash content was detected in the sewage sludge (76.2 %) and paper sludge (82.3 %) biochars in agreement with other studies, and the resulting HHVs were lower than that of the corresponding feedstocks at 5.9 and 3.6 MJ kg −1 , respectively.…”
Section: Resultssupporting
confidence: 91%
“…It comprises counter rotating coaxial screws to move the feed along the reactor and allows for easy control of solid residence time. Heat transfer is aided by the use of metal spheres, negating the need for costly feed preparation associated with fast pyrolysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate pyrolysis (slow heating rates, intermediate solid residence times) is considered to be at the early stages of research and development; however, recent studies have shown that biomass and waste derived intermediate pyrolysis oils can give a product oil with improved properties which are to a certain degree more comparable to biodiesel and diesel fuels [10][11][12][13].…”
Section: Advanced Systems: Biowaste Derived Pyrolysis Oils For Dieselmentioning
confidence: 99%
“…Ouadi et al [10,11,35] recently demonstrated that pyrolysis oils with a low water content of 3−4% and a higher heating value (HHV) of around 36−37 MJ/kg could be produced through intermediate pyrolysis of deinking sludge obtained from both a secondary fibre tissue and newsprint mill.…”
Section: Advanced Chp Application: Dual-fuel Engine Application For Cmentioning
confidence: 99%